Teaching critical literacy in South African English classrooms: Constraints and affordances. Issue 1 (2nd January 2022) - Enslin, Emma
Abstract: Critical literacy is an approach to teaching that addresses the relationship between language and power. This study sought to ascertain whether or not PGCE (Post-Graduate Certificate in Education) graduates from the University of the Witwatersrand were able to apply what they had learned about critical literacy in their English teaching after graduation and how subjective experience, context and identity can influence the ways that teachers take up critical literacy. Three research participants, one of whom was the researcher, provided data on their experiences of attempting to teach from a critical literacy perspective, one in the form of the author's auto-ethnographic narratives and two in the form of interviews. Narrative analysis was applied to all three sets of data. The findings suggest that English teachers in South African schools may be constrained by a chronic lack of time, lack of support from colleagues and institutions for the teaching of critical literacy, the overly prescriptive application of the current curriculum and schools' own particular versions of performativity and accountability cultures. Despite these constraints, teaching critical literacy is eminently possible and efforts to practise critical literacy are aided by cultivating positive relationships with learners.